Evaluation of Survival and Durability of Fixed Prosthodontic Restorations in a Tertiary Dental Centre of Eastern Nepal - Mehta, Pawan; Regmi, Sirish Chandra (Journal of Nobel Medical College, 2024)
Background: Fixed prosthodontic restorations play a pivotal role in dental rehabilitation, providing essential functions such as mastication, aesthetics, and oral health preservation. This study aims to assess the survival of fixed prosthodontic restorations within the context of a tertiary dental centre in Eastern Nepal. Materials and Methods: A retrospective cohort study was conducted among 228 patients, involving a comprehensive analysis of patient records from the tertiary dental centre. Data were collected on patient demographics, types of fixed prosthodontic restorations (e.g., crowns, bridges), materials used, adhesive systems, follow-up durations, and any recorded instances of restoration failure. Patient satisfaction scores, including aesthetic outcomes, comfort, and functionality, were also assessed. Results: The mean age of patients undergoing fixed prosthodontic restorations was 43.1 years, predominantly male (66.7%), with good systematic health (68.4%) and varying levels of oral hygiene. Oral hygiene status, parafunctional habits, restoration type, and subjective experiences such as comfort, functionality, and aesthetic satisfaction were all significantly associated with survival rates (p < 0.001). Conclusion: The results may have implications for clinical decision-making, informing practitioners about the most effective materials and techniques for enhancing the durability of fixed prostheses in this region. Further research and continuous evaluation are crucial for refining prosthodontic practices and ensuring optimal patient care in the unique healthcare landscape of Eastern Nepal.